Can we restore the colour of long‐term discoloured resin composites by noninvasive methods?. Issue 5 (26th May 2020) - Atalayin Ozkaya, Cigdem; Yasa, Bilal; Demirhan, Ali Osman; Turkun, Lezize Sebnem
Abstract: The aim of this study is to investigate the effect of toothbrushing and paste repolishing on the colour restitution of long‐term coffee discoloured prefabricated and direct resin composites. One prefabricated (Componeer‐Coltène) and three direct resin composites (Brilliant Ever Glow‐Coltène, Essentia‐GC, Harmonize‐Kerr) were tested. Componeer samples were prepared with and without polishing while the other groups were all polished. After baseline colour‐measurement, the specimens were immersed in coffee for 3‐month and colour‐measurement was repeated, then a simulation of 1‐year of toothbrushing (Toothbrush Simulation ZM‐3.4‐SD Mechatronics) with Pro‐Expert Professional Protection‐Ipana, 3D White Luxe Perfection‐Ipana, and White Ruscello‐GC toothpaste was performed. Colour‐changes (Δ E ) after toothbrushing and repolishing with polishing paste (Enamelize, Cosmodent) were calculated. The discolouration occurred after prolonged exposure to a coffee solution was above the clinically acceptable level of Δ E = 2 in all groups, except Componeer polished group. The lowest discoloured group was Componeer polished (Δ E = 1.66 ± 0.32) while the highest was Essentia group (Δ E = 4.30 ± 0.48). The samples toothbrushed with White Ruscello exhibited the greatest colour restitution (Δ E = 2.06 ± 0.75) ( P < .05). After paste repolishing, slight colour restitution was observed among all the groups, but the differences between them remained the same as after the toothbrushing procedure. Prolonged exposure to coffee solution affects the colour of the resin composites and noninvasive methods can provide colour restitution below the critical value for visual perception (Δ E = 3.3). Noninvasive procedures such as toothbrushing with a whitening toothpaste or repolishing with a polishing paste may ensure the colour restitution of direct resin composite restorations until a clinically acceptable level.